Case Report: First Two Identified Cases of Fabry Disease in Central Asia - Cainelli, Francesca; Argandykov, Dias; Kaldarbekov, Dauren; Mukarov, Murat; Tran Thi Phuong, Liên; Germain, Dominique P. (Frontiers in Genetics, 2021)
Background: Fabry disease (FD, OMIM #301500) is a rare, progressive, X-linked inherited, genetic disease due to the functional deficiency of lysosomal α-galactosidase (α-GAL) that leads to the accumulation of glycosphingolipids (mainly globotriaosylceramide or Gb3) and its derivative globotriaosylsphingosine or lyso-Gb3). Classic FD is a multisystem disorder which initially presents in childhood with neuropathic pain and dermatological, gastrointestinal, ocular, and cochleo-vestibular manifestations. Over time, end-organ damage such as renal failure, cardiac arrhythmia and early stroke may develop leading to reduced life expectancy in the absence of specific treatment. Case presentation: We describe two Kazakh patients who presented in adulthood with a delayed diagnosis. We conducted also a family screening through cascade genotyping. Conclusion: This is the first description of cases of Fabry disease in Central Asia. An extensive family pedigree enabled the identification of ten additional family members. Patients with rare genetic diseases often experience substantial delays in diagnosis due to their rarity and non-specific symptoms, which can negatively impact their management and delay treatment. FD may be difficult to diagnose because of the non-specificity of its early and later-onset symptoms and its X-linked inheritance. Raising awareness of clinicians is important for earlier diagnosis and optimal outcome of specific therapies.